Estudo da viabilidade sensorial do enriquecimento com ferro de vários produtos derivados de soja e a quantificação de seus teores em isoflavonas - Mendonça, José Eduardo de [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
A deficiência de micronutrientes afeta de maneira substancial o estado nutricional, a saúde e o desenvolvimento de uma parcela significativa da população de países desenvolvidos e em desenvolvimento. Os minerais, entre eles o ferro, desempenham funções essenciais à vida, o que justifica a grande atenção dada as carências deste nutriente. Dentre as estratégias utilizadas para o combate e prevenção das carências nutricionais, o enriquecimento de alimentos de baixo custo ou de grande consumo pelos grupos mais vulneráveis, tem se apresentado como uma alternativa eficaz. Resultados expressivos de redução dos casos de anemia ferropriva vêm sendo alcançados em programas de Política Nacional de Alimentação que prevêem a adoção de medidas essenciais, como o enriquecimento de alimentos amplamente utilizados pela população, tais como, o pão e o leite....

The deficiency of micronutrients affects substantially the nutricional state, the health and the development of a significant part of the population, both in developed and in developing countries. Minerals, among them the iron, play vital roles in life, which accounts for the great attention that has been given to the lack of these nutrients. Among the strategies used for prevention of malnutrition, the enrichment of low cost foods or greatly consumed ones by the most vulnerable groups has been shown as an efficient alternative. Outstanding results of reduction in cases of iron deficiency anemia have been reached in the Food National Politics programs that imply the adoption of essential policies, as for the enrichment of food widely consumed by the population, such as bread and milk. Therefore, the purpose of this paper was to study the sensorial viability of enrichment of low cost soy produts , such as milk, bread, yogurt ice cream and peanut candy like, from several sources of iron, as well as to quantify, through HPLC, the isoflavone contents in these products, aiming, if necessary, a further supplementation of those ones. The products have been enriched with three sources of iron FeSO4.7H2O, iron aminoacid chelate and NaFeEDTA and evaluated on the sensorial properties (difference from control and acceptance test) compared with a non-enriched sample (control). Isoflavones have been quantified through HPLC in a first stage in the products enriched with the three sources of iron and were subsequently analyzed in the following materials: soy grains with rind, peeled and cooked soy, okara soy residues, pasteurized soy milk and soy yogurt...(Complete abstract, click electronic address below).
Keywords: Leite de soja - Análise sensorial; Isoflavonas; Ferro; Iron; Soy produts; Isoflavones analysis